Typology of Tourist Villages in Batu City Based on Cluster Analysis: Strategic Implications for Tourism Management - Adya Hermawati; Armanu Thoyib; Triana Dewi Salma; Aviv Yuniar Rahman; Rizki Dwi Ariyanto; Rizki Dwi Farotul Khasanah (Journal of Education and Teaching Learning, 2026)
Tourist villages play a strategic role in boosting local government revenue and ensuring equitable economic distribution among communities; however, uniform management approaches are often ineffective due to variations in potential and performance across villages. This study aims to identify the typology of tourist villages in Batu City based on eight tourism management variables: tourism facilities, infrastructure and accessibility, service quality, creative economy innovation, visitor satisfaction, entrepreneurial orientation, tourist visits, and competitive advantage. Primary data were collected through a questionnaire survey involving 1,152 respondents representing 384 Neighborhood Associations (RT) across 24 villages/sub-districts in three districts of Batu City, namely Batu District, Bumiaji District, and Junrejo District. Sample selection employed a proportional stratified sampling technique. The analytical methods used were a Systematic Literature Review to identify the research variables, followed by Cluster Analysis to group the villages/sub-districts based on similarities in their characteristics. The results indicate that the 24 tourist villages/sub-districts in Batu City can be classified into three clusters: Cluster 2 as the high-performing group (mean = 4.389), Cluster 1 as the moderate group (mean = 3.969), and Cluster 3 as the low-performing group (mean = 3.758). Each cluster exhibits significant differences in characteristics across all measured variables. These findings imply that development strategies for tourist villages must be differentiated and typology-based rather than uniform, ensuring that tourism management policies are more targeted and have a tangible impact on enhancing the competitive advantage of tourist villages in Batu City.